The Influence of the Board of Commissioners, Institutional Ownership, and Managerial Ownership on the Firm Value of Non-Banking State-Owned Enterprises - Prasetyo, Deny; Kufepaksi, Mahatma; Dalimunthe, Nindytia Puspitasari (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
This study examines the influence of corporate governance mechanisms—specifically the Board of Commissioners, Institutional Ownership, and Managerial Ownership-on the firm value of non-banking state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange from 2014 to 2023. Using a panel data regression model based on purposively selected samples of 15 firms over a ten-year period, the results indicate that while institutional and managerial ownership significantly enhance firm value, the size of the board of commissioners does not exert a statistically significant effect. The findings highlight the importance of active monitoring by institutional investors and alignment of managerial interests with shareholders in improving corporate performance. These insights contribute to understanding effective governance practices in SOEs and offer practical recommendations for policy-makers aiming to enhance transparency and accountability within Indonesian state-owned enterprises.